The Ministry of Health (London : Co-operative Printing Society)
1919 1919 1910s 18 pages III. THE MINISTRY OF HEALTH. The Ministry of Health Sub-Committee held eight meetings, and considered the main problems in connection with this matter. The conclusions reached represent the general mind of the Committee, though individual members would be ready to recommend a more drastic policy. It is felt, however, that the steps outlined in this report do not preclude wider developments in the future, should these be found necessary and desirable. The members of the Sub-Committee are at one in believing a Ministry of Health to be urgently necessary in order to secure greater co-ordination and efficiency in respect of public health. They are at one also in recommending that the best medical science and advice should be freely open to all. They believe that any scheme to be effective must carry with it the co-operation and goodwill of the medical profession as a whole, especially of the general medical practitioner. To this end it is necessary that over-centralisation and bureaucracy should be avoided, that local and popular control should be ensured, regard being paid to local circumstances, and that the medical profession should have direct representation on the authorities for the promotion of public health, and full opportunity for a collective expression of their views. There should be established by legislation a Ministry of Health having a general supervision over all matters relating to health, with a Minister responsible to Parliament, and having a seat in the Commons. A skeleton Bill to be clothed afterwards by regulations and Orders in Council will not meet the case. The scope and functions of the new authority should be defined in some detail in the Parliamentary Bill. With respect to the transfer of the health functions now undertaken by other Government Departments, the following recommendations are made: — 1. Local Government Board. — All the health functions of the Poor Law should be transferred to the Ministry of Health, and it should undertake such other functions of the Local Government Board as concern Infectious Disease and Public Health Acts; vaccination; port sanitation and quarantine; appointments of officers of local authorities under Public Health and Vaccination Acts; law relating to food and sale of drugs, milk, and meat; purity and sufficiency of water supply; Provisional Order under Public Health Acts; the whole provision as to the campaign against tuberculosis; bye-laws under Public Health, Highways, Housing, Burial, and other Acts turning on sanitation; congresses and conferences. 2. National Insurance Commission. — The administration of all the functions of the National Insurance Commission other than those relating to the disbursement of Sickness, Disablement, and Maternity cash Benefits, and to Unemployment Insurance, should be transferred to the Ministry of Health. 14 36/H24/6